Bunchy TiO2 hierarchical spheres with fast electron transport and large specific surface area for highly efficient dye-sensitized solar cells. (May 2016) - Song, Dandan; Cui, Peng; Wang, Tianyue; Xie, Bixia; Jiang, Yongjian; Li, Meicheng; Li, Yaoyao; Du, Sheng; He, Yue; Liu, Zhuohai; Mbebgue, Joseph Michel
Abstract: The exploration of TiO2 nanostructures with fast electron transport and large specific surface area is essential for their applications in solar cells. For this aim, bunchy TiO2 hierarchical spheres (BS-TiO2 ), consisting of multiple TiO2 microspheres constructed by nanosheets and the 1D TiO2 nanobelt, were rationally designed and fabricated. BS-TiO2 enables the much fast charge transport properties in the photoanode (with a long electron diffusion length of 36 μm) and shows large specific surface area (higher than 200 m 2 /g), leading to excellent electron collection and light harvesting, which enable the increased conversion efficiency of the dye-sensitized solar cell by 34% for BS-TiO2 photoanode (7.5%) compared to nanoparticle (P25) photoanode. This work provides an important approach for the rational design of the TiO2 nanostructures, which also implies the application of the bunchy TiO2 hierarchical spheres in other type of solar cells, artificial photosynthesis, and other optoelectronic applications. Graphical abstract: Highlights: Bunchy TiO2 spheres (BS-TiO2 ) contain multiple nanosheet microspheres and nanobelt. BS-TiO2 shows large surface area (>200 m 2 /g) and fast charge transport as photoanode. BS-TiO2 photoanode enables higher device efficiency (7.5%) than P25 photoanode.